REVENGE PORN IN INDONESIAN HIGHER EDUCATIONS: GENDER-BASED PERSPECTIVE - Nurdin, Nurdin (LPPM Institut Pendidikan Nusantara Global, 2023)
The advances in information and communication technology have many benefits for everyone in everyday life. The use of the internet to surf information by the Indonesian people is extremely high, including universities students. The convenience provided by smartphones to many groups is also inseparable from the negative impact that stalks internet users (social media) in Indonesian universities in the form of online sexual violence. Along with the massive spread of COVID-19 from 2020 to 2021, this negative impact has been transformed into the form of online gender-based sexual violence on various campuses. Revenge porn is the spreading of sexual information that is displayed in the form of pictures, photos or videos. Revenge porn is included in cases of sexual violence, where the victims are not only women but also men, can also become victims of the revenge porn act. These actions have been widely carried out to make victims famous by dropping victims psychologically and physically. This phenomenon has finally caused polemics both internally and externally on campus in responding to the challenges of the high number of online gender-based sexual violence cases. The purpose of this study is to examine the social, cultural, legal, and political aspects of the high number of revenge porn cases in universities in Indonesia.